Effect of Various Parameters on Seismic Response of CBM Structures: A Numerical Investigation - Shandilya, A. N. (2024)
Confined brick masonry (CBM) structures have demonstrated success in seismic regions due to their straightforward construction and efficient wall-to-column connections. However, there is not enough comprehensive understanding about how these structures respond to changes in geometry and material. Addressing this gap, our study employs a robust numerical technique, utilizing an integrated finite element macromodel. In this approach, we treat wall and tie members as a unified entity, enhancing computational efficiency. The concrete damage plasticity method is applied to predict the evolution of CBM wall damage, with a subsequent pushover analysis conducted to ascertain seismic capacity and response reduction factor. This factor is further used as a criterion to appraise the performance and seismic response of CBM walls. An extensive parametric study is carried out that compares the response of CBM wall with reinforced concrete (RC) infill wall, examines the impact of different opening sizes and confinement schemes around openings in CBM walls, and considers various masonry material properties. The study presents insights into damage propagation of CBM walls under seismic action particularly for cases of opening, confinement around opening, and material type. Findings indicate the superiority of CBM structures over RC infill walls, especially in earthquake-prone regions. Crucially, confinement around openings is identified as a pivotal factor in restoring lost strength, with Scheme A and E emerging as structurally and economically viable optimal confinement schemes. Furthermore, this study underscores the importance of selecting appropriate masonry type and mortar mix proportions in designing CBM walls for seismic resistance.